The impact of social media influencers purchase intention in the Philippines - Dalangin, Jerico John G.; McArthur, James M.B.; Salvador, Jan Benedict M.; Bismonte, Angelika B. (Jurnal Studi Komunikasi, 2021)
The study aims to determine consumers' perception of the advertising efficacy of social media influencers regarding their purchase intention. The researcher believes that specific strategies and skills should be customised to attract consumers' buying intention for an influencer to be effective across social media. The study adopted the "social media influencer questionnaire" developed by Xin Jean Lim. It is an organised questionnaire designed to assess and analyse the effectiveness of social media influencers connected to consumers' purchase intention. A total of 200 respondents from NCR, Metro Manila, participate in this study, with 129 female participants, 71 male participants and mostly from 18 to 24 years old. The respondents' assessment implies that an influencer who establishes most of their honesty and is trustworthy can change consumers' behaviour and purchase intention. Attractiveness and relationships with the product are seen to be also adequate. The respondents' assessment also implies that there is an optimistic and agreeable attitude towards the different advertising efficacy of an influencer for the purchase intention of consumers. Furthermore, there is a significant relationship between the advertising effectiveness and purchase intention of consumers. Female respondents have a higher perception of social media influencers than male respondents because women use the internet more often.